Assessing the success of the first cheetah reintroduction in Malawi. Issue 4 (20th July 2022) - Sievert, Olivia; Fattebert, Julien; Marnewick, Kelly; Leslie, Alison
Abstract: In an effort to restore parts of their historical geographical range, and in recognition of their ability to restore ecosystem functioning and of the financial benefits they can provide through ecotourism, large carnivores have been reintroduced in many protected areas from which they were previously extirpated. Similar to dispersing animals, translocated individuals often undertake long-distance exploratory movements before establishing home ranges. Post-release monitoring of reintroduced carnivores is common, but the mechanisms of population establishment are rarely examined, limiting our understanding of reintroduction success. We monitored survival and post-release movements of seven cheetahs Acinonyx jubatus reintroduced to Liwonde National Park, Malawi, to evaluate early population establishment. Exploratory phases post-release lasted 29–174 days. Duration of pre-release holding periods in the boma had no significant effect on daily distance moved. Males travelled significantly farther and established home ranges later than females. All cheetahs showed release site fidelity and all females birthed their first litter within 4 months of release. Within 2 years of reintroduction, the newly established population consisted of 14 cheetahs, with demographic attributes similar to those recorded in the source populations. Based on individual settlement, survival and reproduction rates, we deemed this reintroduction successful in re-establishing a breeding population of cheetahs in Liwonde. Our findings suggest the drivers of settlement and population establishment for reintroduced cheetahs are complex, highlighting the importance of assessing and reporting post-release monitoring data.